Reliable mortality statistics in Myanmar: a qualitative assessment of challenges in two townships - Myitzu Tin Oung; Kerry Richter; Pramote Prasartkul; Yadanar Aung; Kyaw Thu Soe; Thuzar Chit Tin; Viroj Tangcharoensathien (BMC, 2019)
Abstract Background The vital registration system is universally recognized as the main source of mortality data which is essential for policy formulation, proper interventions and resource allocation to address priority health challenges. To improve availability and quality of mortality statistics by strengthening the vital registration system, understanding the current vital registration system is essential. This study identified challenges in generating reliable mortality statistics in the vital registration system of Myanmar. Methods Qualitative methods were used to collect data in two selected townships of Mandalay Region. Grey literature related to the management of mortality registration was reviewed; in-depth interviews of sixteen key informants and fourteen focus group discussions were conducted with those involved in death registration at the local level, such as healthcare providers, local administrators and knowledgeable adults in households where deaths occurred during the past three years. Thematic analysis was performed to identify system barriers in the death registration process. Results Weaknesses in the death registration system are classified in three areas: a) administrative which includes the lack of enforcement of mandatory death registration, limited issuance of death certificates and no formal mandatory notification of death events by households and; b) technical which includes absence of proper and regular on-the-job trainings, ineffective cause-of-death certification practice for deaths in the communities and the absence of routine data plausibility checks at the local level; and c) societal which includes poor community awareness and inadequate participation in death registration. Conclusion The study highlighted challenges in the death registration system at the operational level, which undermines the achievement of a satisfactory level of completeness and accuracy of mortality data. We recommend establishing a strong legal framework, improving technical capacities and raising public awareness and cooperation to strengthen the system that can generate reliable mortality statistics.